ANALISIS PENGARUH DAYA DUKUNG LINGKUNGAN BUDIDAYA TERHADAP LAJU PERTUMBUHAN UDANG VANAME (L. vannamei) - Heri Ariadi; Benny Diah Madusari; Dewi Mardhiyana (EnviroScienteae, 2022)
The aquaculture carrying capacity is the optimum capacity of the environment to accommodate the waste load that exists in the aquaculture ecosystem. The purpose of this research was to determine by the relationship and influence of the environmental carrying capacity of aquaculture ecosystems on the growth rate of vannamei shrimp (L. vannamei) based on dynamic modelling analysis. The research study method used in this study was an ex-pose facto causal design with the observed research indicators being water quality parameters and shrimp biological parameters. The results showed that during shrimp culture periods, the water quality indicators were still in accordance with the water quality standard values for aquaculture activities, except for the organic matter parameter which had a concentration of 93.48 mg/L (±17.02). Meanwhile, the shrimp growth rate continues to increase in an aggregate manner at an additional rate of 0.16 g/day. Shrimp growth rate has an opposite relationship with the percentage of feed rate described by the equation Y=0.180-0.001x. Then in another analysis it was stated that the shrimp growth rate in ponds was closely related to the environment carrying capacity of 71.5%. From the study results it can be concluded that there is a strong and mutually influencing relationship between with shrimp growth rate and the pond environment carrying capacity, which is described by the fluctuation pattern of the dynamic model that runs in rhythm.